The Degree of application of productive thinking skills by sixth- grade students in Social Studies, “a Field Study in the City of Lattakia” (Latakia University (formerly Tishreen) Journal for Research and Scientific Studies - Arts Humanities Series, 2026)
The Research Aimed To Identify The Degree To Which Sixth – Grade Students In Latakia Puplik Schools Apply   Productive Thinking Skills In Social Studies, The Descriptive Approach Was Used To Achieve The Research Objectives. The Researcher Also Prepared A Productive Thinking Skills Questionnaire Containing Of 22 Statements Distributed Across (4) Sub- Domains, As Follows (7) Statements For Fluency Skills And The Same For Flexibility Skills. (6) Statements For Originality Skills And The Same For Evaluating Discussions, Each Statements Has Five Alternatives. After Verifying The Psychometric Properties Of The Questionnaire (Validity, And Reliability), And Its Application To A Sample Of (266) Male And Female Learners For The Academic Year 2024-2025The Researcher Reached Several Key Findings, Including: The Learner, S Application Of Productive Thinking Skills In Social Studies Was At An Avererage Level (2,84), There Is A Disparity In Learner S Application Of Productive Thinking Skills With The Skill Of Discussions Evaluating Scoring Highly At (3,7),  The Originality Skill Was At An Average Level Of (3), The Flexibility Skill Was At (2,7),And The Fluency Skill Was At A Low Level Of (2,2)
Keywords: Productive Thinking Skills, Sixth Grade Learners, Social Studies